ANALISIS KOMPARATIF PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MASKARA WARDAH DAN MAYBELLINE DI KOTA SEMARANG - Putri, Anggia Rindra; Prihatini, Apriatni Endang (Jurnal Ilmu Administrasi Bisnis, 2019)
Mascara is a cosmetic product needed by women to perfect their appearance. As a brand that is quite prominent in Indonesia and dominates the market, Wardah and Maybelline compete to create products in accordance with consumer expectations. However, Wardah has not been able to surpass Maybelline for mascara products. As for products other than mascara, Wardah tends to dominate the market. This study aims to determine the effect of product quality and prices on purchasing decisions of Wardah and Maybelline mascara. This type of research is explanatory research and sampling uses nonprobability sampling techniques, purposive sampling method. Data collection using questionnaires and google form. The sample used was 200 respondents using Wardah and Maybelline mascara in the city of Semarang. This study uses quantitative and qualitative analysis with validity, reliability, correlation coefficients, coefficient of determination, simple and multiple regression, significance of t test and F test, normality test and Mann Whitney test. The results of the study show that the variables of product quality and price have an effect on purchasing decisions. The variable correlation coefficient of product quality and price for Wardah mascara has a strong relationship, Maybelline mascara has a moderate relationship. The determination coefficient of product quality variable on Wardah mascara purchasing decision variable is 39.1%, Maybelline mascara is 25.6%. The determination coefficient of the price variable on the variable purchase decision of Wardah mascara was 42.6%, Maybelline's mascara was 27.2%.